Branch-type intraductal papillary neoplasm of the bile duct treated with laparoscopic anatomical resection: a case report - Rumi Matono; Mizuki Ninomiya; Kazutoyo Morita; Takahiro Tomino; Yumi Oshiro; Tomoyuki Yokota; Takashi Nishizaki (Surgical Case Reports)
Abstract Background Intraductal papillary neoplasm of the bile duct (IPNB) is characterized by an intraluminal, growing papillary tumor covered by neoplastic biliary epithelial cells with a fine fibrovascular core. IPNB was introduced as a precancerous and early neoplastic lesion in the 2010 World Health Organization classification of tumors of the digestive system. IPNB eventually invades the bile duct wall and progresses to invasive cholangiocarcinoma. IPNB resembles intraductal papillary mucinous neoplasm of the pancreas (IPMN), particularly the main pancreatic duct type. IPNB cases, possibly corresponding to branch-type IPMN, have been recently reported, and these cases involved the peribiliary glands significantly and showed gross cystic dilatation. Small branch-type intrahepatic IPNB often mimics simple liver cysts, making the diagnosis of IPNB difficult. Some literature recommended surgical resection for treatment. Laparoscopic resection is a good treatment option for small tumor. We herein present the case of branch-type IPNB that was treated with laparoscopic anatomical liver resection 5 years after being detected. Case presentation A 64-year-old woman was undergoing follow-up for primary aldosteronism. In 2012, follow-up computed tomography (CT) incidentally revealed a 7-mm cystic lesion in segment 8 of the liver. From 2012 to 2017, the cystic lesion kept increasing in size, reaching 17 mm. In 2017, CT also revealed a 13-mm mural nodule in the cyst wall. Therefore, the patient was referred to our department for possible malignancy. We suspected a branch-type IPNB; however, the mass was small and diagnosis could not be made without performing biopsy. Accordingly, surgical resection was performed for diagnosis and treatment. Because branch-type IPNB might show horizontal spread through the intrahepatic bile duct, we believed that anatomical resection of the liver was appropriate considering the malignant potential of the lesion. Therefore, laparoscopic anatomical resection of segment 8 of the liver was performed. The resected tumor measured 17 mm and was histologically diagnosed as a high-grade IPNB. Conclusion Branch-type IPNBs are rare but can potentially lead to malignant tumors. Surgical resection is the treatment of choice, with laparoscopic anatomical resection being a good treatment option for this small tumor.